2023
DOI: 10.3390/jrfm16020075
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Procedural Justice on Turnover Intention and Social Loafing Behavior among Hotel Employees

Abstract: This study examines the influences of procedural justice on the turnover intention and social loafing behavior among employees in the hotel industry. Despite a growing body of literature regarding the relationship between organizational justice, turnover intention and social loafing, there is limited published research on the influence of procedural justice on social loafing behavior among hotel employees with the mediating effect of turnover intention. For this purpose, a questionnaire was self-administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Its low scores can reduce productivity by negative emotions experienced among employees such as anger [33]. It has been proven, for example, that in the case of hotel staff, procedural justice influences turnover intention [34]. The results also showed that organizational justice has an important effect on sustainable employee development, builds motivation, and benefits business as a result [35][36][37].…”
Section: Discussionmentioning
confidence: 98%
“…Its low scores can reduce productivity by negative emotions experienced among employees such as anger [33]. It has been proven, for example, that in the case of hotel staff, procedural justice influences turnover intention [34]. The results also showed that organizational justice has an important effect on sustainable employee development, builds motivation, and benefits business as a result [35][36][37].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown how job characteristics are associated with meaningful work (Hackman & Oldham, 1975 and that workers who view their jobs as significant and meaningful are more committed and less likely to leave (Wingerden & Stoep, 2018;Holbeche & Springett, 2004). Further, procedural justice can reduce employees' intentions to leave; it significantly and negatively influences turnover intentions (Edrees, Sobaih, Gharbi, & Abu Elnasr, 2023). Thus:…”
Section: Impact Of Procedural Justicementioning
confidence: 99%
“…It is worth noting that organizational trust has never been so much in demand in a configuration now governed by scepticism and disloyalty. Edrees et al (2023) defined turnover as a conscious and deliberate attitude toward leaving an organization. It is essential to note that previous studies revealed many variables that affect an individual's turnover intention, such as organizational justice (Hom et al, 2017), mainly procedural justice (Gharbi et al, 2022a;, psychological safety (Sobaih, Gharbi, et al, 2022), leadership style (Sobaih, Hasanein, et al, 2022), and mistrust (Gharbi et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%